INVESTIGATING EFL LEARNERS’ READING COMPREHENSION PROBLEMS AND STRATEGIES IN TIDAR UNIVERSITY - Ikrar Genidal Riadil (Universitas Sarjanawiyata Tamansiswa, 2020)
This study deals with Teaching English as a Foreign Language (TEFL) of reading skills in EFL learners of Tidar University. This study is to investigate the problems and to determine the strategies of reading that the learners use to help them according to their reading problems. This study seeks to answers two research questions: (1). What are/is the problems of reading comprehension at Tidar University? (2). What are/is the strategies that EFL learners use to help them in reading comprehension problem? This study adopted a descriptive qualitative approach that used a questionnaire to complete this research. The aims of this study are to know the factors of reading comprehension factors and to know EFL learners' strategies that they use to help their in reading comprehension in Tidar University.